Psychological and Social Support Among Chronic Kidney Disease Patients: A Qualitative Study - Komariah, Euis Dedeh; Sili Beda, Nikodemus; Novia, Kristia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Chronic kidney disease is one of the chronic diseases that can affect mental health because the patient must undergo dialysis in addition to kidney transplantation to survive. Purpose of this study was to explore the perspectives of chronic kidney disease patients undergoing dialysis regarding mental health and social support. This study used a qualitative method with a descriptive phenomenological approach. The population in this study was 30 patients with chronic kidney disease, 10 patients became participants were interviewed with semi-structure. Samples were captured by the purposive sampling method. The results of the study were analyzed by the Colaizzi method. Based on interviews regarding the perspectives of patients with chronic kidney disease, two main themes were identified, namely psychological state and social support. Chronic kidney disease patients undergoing dialysis face challenges and difficulties related to their psychological state.